### 7 Answers

4y – y + 11 = 38

3y = 38 – 11

3y = 27

y = 27/3

y = 9

Y=9

first you combine like terms:

4y-y+11=38: you subtract 4y by y making it 3y

now the equation looks like this:

3y+11=38

then you subtract 38-11 making it 27.

then you divide 27 by 3 leaving the y by itself,

making y=9.

4Y – Y + 11 = 38

3Y = 27

Y = 9

4y-y+11=38

3y+11=38

3y=27

y=9

y= 9

Check :

4(9) = 36

36-9 = 27

27+11=38

y=9

Source(s): My knowledge lol .y=9

4y-y=3y

then you have 3y+11=38

then subtract 11 from both sides then you get 3y=27

then divide both sides by 3 and y=9

hope this helps

Source(s): ap calculus